Integrating Customized Geographical Data Into Google Earth - Hu, Chenwei (The University of Edinburgh, 2011)
The objective of this project is to develop an interactive WebGIS for North Atlantic scholars by providing geographic data services of converting, downloading, sharing, visualizing and analyzing data. A Web-based application system is produced to allow the North Atlantic scholars to upload their customized geographic data (in shapefile or CSV file format) through a simple web surface. Uploaded data will be converted into KML as well as shapefiles or CSV files, and the users will be able to download these files and then visualize their data in Google Earth. Various languages and programmes were used in this project, including Oracle RDBMS, SQL, Perl, HTML and KML. The Web-based tool provides users with limited GIS knowledge the ability to use geobrowsers to analyze customized geodata from different formats.